Diagnostic value of motor evoked potential parameters in patients with Parkinson’s disease stage II - A. V. Demchenko; Dzh. N. Aravitska (Patologìâ)
The aim of our study was to identify the most informative parameters of motor evoked potential (MEP) based on clinical and neurophysiological comparisons in patients with Parkinson’s disease (PD) stage II.